WHY ECONOMIC PERFORMANCE HAS DIFFERED BETWEEN BRAZIL AND CHINA? A COMPARATIVE ANALYSWHY ECONOMIC PERFORMANCE HAS DIFFERED BETWEEN BRAZIL AND CHINA? A COMPARATIVE ANALYSIS OF BRAZILIAN AND CHINESE MACROECONOMIS OF BRAZILIAN AND CHINESE MACROECONOMIC POLICY - Ferrari-Filho, Fernando; Spanakos, Anthony (Revista Venezolana de Análisis de Coyuntura, 2016)
Tliis paper adresses a specific question: why has China grown so rapidiy and Brazil not? To answerthis question, it (i) establishes the basis for comparison between China and Brazil by contextualizingthese countries within the BRICs concept, and (ii) presents a comparativa anaiysis ofBrazilian and Chinase raforms focusing oniy on the issue of macroeconomic policy, especiailythe monetary and exchange rata ragimas, and its affect on growth.